FASIES DAN DIAGENESA FORMASI GAMPING-WUNGKAL DI DAERAH BAYAT, KLATEN JAWA TENGAH - Mulyadi, Dedi; Siregar, M. Safei; -, Praptisih (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2008)
The limestone of Wungkal Formation is the old tertiary sedimentary rocks existing between the metamorphic rock in Bayat complex, Klaten, Central Java.A thin section analysis was conducted on the limestone samples resulted in two facieses of carbonates, the foraminifera packstone and the foram-algal packstone. The diagenesis process includes microbal micritisation, cementation, dissolution and com-pacttion. Diagenesis occurred from marine environment, fresh water and burial. The for-mation of the Wungkal formation limestone took place during the mid Eocene to late Eo-cene at the basin slope of the shallow to slightly deep marine environment.